INTERFERON GAMMA AND INTERFERON GAMMA INDUCIBLE PROTEIN-10 IN DETECTING TUBERCULOSIS INFECTION - Kabeer, Basirudeen Syed Ahamed (2012)
OBJECTIVE: This study aimed to compare the levels of TB-antigen specific Interferon gamma (IFN-γ) and IFN-γ inducible protein (IP)-10 in culture of whole blood samples from healthy controls (HC) and healthy household contacts (HHC). METHODOLOGY: A total of 386 study subjects, which included 186 HC and 200 HHC, were recruited. QuantiFERON TB-Gold in-tube (QFT-IT) assay was employed to measure IFN-γ levels. IP-10 levels were measured in the supernatants collected from QFT-IT tubes. Tuberculin skin test was also performed. RESULTS: The levels of TB antigen specific IFN-γ and IP-10 were significantly higher in HHC compared to HC. There was no significant difference observed between positivity of QFT-IT and IP-10 in HC and HHC. The positivity of TST was significantly lower in subjects <17 year, when compared to IP-10 (p<0.005). The reduced cut-off point 0.22 IU/ml significantly increased the positivity of QFT-IT among children with high risk for latent TB infection (LTBI). CONCLUSIONS: Measurement of TB antigen specific IFN-γ and IP-10 can be potential markers for the detection of LTBI.